2019
DOI: 10.2140/moscow.2019.8.193
|View full text |Cite
|
Sign up to set email alerts
|

Integer complexity: the integer defect

Abstract: Define n to be the complexity of n, the smallest number of ones needed to write n using an arbitrary combination of addition and multiplication. John Selfridge showed that n ≥ 3 log 3 n for all n, leading this author and Zelinsky to define the defect of n, δ(n), to be the difference n − 3 log 3 n. Meanwhile, in the study of addition chains, it is common to consider s(n), the number of small steps of n, defined as ℓ(n) − ⌊log 2 n⌋, an integer quantity. So here we analogously define D(n), the integer defect of n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The proofs of Proposition 4.3 and Theorem 1.9 uses a similar idea to the earlier proofs of (1.6), proven in [3], and (1.8), proven in [5]. Those were both also cases where, to get a lower bound on the order type of a particular set of defects, it was shown that particular low-defect polynomials "usually" yield numbers which have the complexity one would expect; and this in turn was proven by noting that unless this were so, this would violate a known upper bound on the order type of a smaller set of defects.…”
Section: Bonus Theoremmentioning
confidence: 96%
See 3 more Smart Citations
“…The proofs of Proposition 4.3 and Theorem 1.9 uses a similar idea to the earlier proofs of (1.6), proven in [3], and (1.8), proven in [5]. Those were both also cases where, to get a lower bound on the order type of a particular set of defects, it was shown that particular low-defect polynomials "usually" yield numbers which have the complexity one would expect; and this in turn was proven by noting that unless this were so, this would violate a known upper bound on the order type of a smaller set of defects.…”
Section: Bonus Theoremmentioning
confidence: 96%
“…Why do we call such polynomials "substantial"? In making this definition, we build upon the technique used earlier in [5]. Suppose that η ∈ D, and suppose it takes the form δ(f ) for some low-defect polynomial f (which it always will, but which we of course have not yet proven at this point in the paper).…”
Section: Bonus Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…Numbers are one of the basic knowledge in mathematics. Numbers are a mathematical concept used for solving and measuring (Altman, 2019;Davarpanah & Mirshekari, 2019;Dudley & Dudley, 2012;Tristianto, Linawati, & Susanto, 2018). Symbols or symbols used to represent a number are called numbers or symbols.…”
Section: Introductionmentioning
confidence: 99%